Alternating teacher's development in Countryside Education Undergraduate courses at UNB and UFMG - Mônica Castagna Molina; Maria de Fátima Almeida Martins; Maria Isabel Antunes-Rocha (Universidade Federal do Norte do Tocantins, 2021)
The article deals with the forms of organization of time, space and content developed in teacher's development courses in Countryside Education at University of Brasília and Federal University of Minas Gerais. It starts with the reflection that these experiences are producing formative processes that enable the dialogue among the university, the school and the communities in a socio-territorial perspective. The proposed discussions are based on the authors' experience in teaching, extension, research and publications activities within the scope of the courses. Initially, the concepts of Alternation Pedagogy and Alternation Development are defined. Then the courses and their forms of alternation organization are described and analyzed. To conclude, it is registered that this formative proposal allows the exercise of the protagonism of the participants and the countryside contexts in the perspective of education as a right and as an instrument to enable the articulation among the school, the countryside and the society projects in an emancipatory perspective.